Comparative evaluation of 2% turmeric extract with nanocarrier and 1% chlorhexidine gel as an adjunct to scaling and root planing in patients with chronic periodontitis: A pilot randomized controlled clinical trial - Sanjeela Rakshith Guru (Journal of Indian Society of Periodontology, 2020)
Context: Nanoparticles, owing to their smaller size, penetrate regions inaccessible to other delivery systems, such as periodontal pockets. Thus, the present study aimed to comparatively evaluate efficacy of 2% curcumin with nanocarrier and 1% chlorhexidine gel as a local drug delivery (LDD) in the treatment of periodontal pockets. Materials and Methods: Forty-five chronic periodontitis patients with pocket depth 5–7 mm in two or more teeth were selected. Full-mouth scaling and root planing (SRP) was done for all patients followed by random allocation to the three treatment groups, namely SRP group (Group 1), 2% curcumin with nanogel (Group 2), and 1% chlorhexidine gel (Group 3). Clinical parameter assessment and microbiological analysis of subgingival plaque samples for Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), and Tannerella forsythia (Tf) was done at baseline, 21st day, and 45th day. Results: The results showed that when the two LDD agents were used as an adjunct to SRP in chronic periodontitis, there was an improvement in all clinical parameters. Evaluation of microbiological parameters also showed a significant reduction in Aa, Pg, and Tf levels. Comparison of 2% turmeric extract with a nanocarrier system with 1% chlorhexidine gel showed that both the agents had a comparable antibacterial effect on the three selected periodontopathic bacteria. Conclusion: The present study showed that both the LDD agents showed an effective improvement of clinical and microbiologic parameters. 2% curcumin delivered with a nanocarrier system showed results comparable to chlorhexidine gel and hence shows promising future as an LDD agent in the treatment of periodontal pockets.